REFLEXÕES SOBRE A UTILIDADE DO ENSINO DA GRAMÁTICA TEÓRICA PARA O DOMÍNIO DA NORMA-PADRÃO - Silva, Elizabeth Ramos da (Intercâmbio, 2010)
This text presents an interdisciplinary exploration about the grammar teaching importance in order to dominate the standard language. Vygotsky’s and Lipman’s concepts, as well as the contemporary linguists, confirm that the systematic teaching of grammar, if used on a significative way, could be very important to the child’s cognitive development.